Circalunar variations of the night sky brightness – an FFT perspective on the impact of light pollution. Issue 2 (16th December 2019) - Puschnig, Johannes; Wallner, Stefan; Posch, Thomas
ABSTRACT: Circa-monthly activity conducted by moonlight is observed in many species on Earth. Given the vast amount of artificial light at night (ALAN) that pollutes large areas around the globe, the synchronization to the circalunar cycle is often strongly perturbed. Using 2-yr data from a network of 23 photometers (Sky Quality Meters; SQM) in Austria (latitude ∼48°), we quantify how light pollution impacts the recognition of the circalunar periodicity. We do so via frequency analysis of nightly mean sky brightnesses using Fast Fourier Transforms. A very tight linear relation between the mean zenithal night sky brightness (NSB) given in $\mathrm {mag_{SQM}\, arcsec^{-2}}$ and the amplitude of the circalunar signal is found, indicating that for sites with a mean zenithal NSB brighter than 16.5 $\mathrm {mag_{SQM}\, arcsec^{-2}}$ the lunar rhythm practically vanishes. This finding implies that the circalunar rhythm is still detectable (within the broad bandpass of the SQM) at most places around the globe, but its amplitude against the light polluted sky is strongly reduced. We find that the circalunar contrast in zenith is reduced compared to ALAN-free sites by factors of $\frac{1}{9}$ in the state capital of Linz (∼200 000 inhabitants) and $\frac{1}{3}$ in small towns, e.g. Freistadt and Mattighofen, with less than 10 000 inhabitants. Only two of our sites, both situated in national parks (Bodinggraben and Zöblboden), show natural circalunar amplitudes. At our urban sites, we further detect a strong seasonal signal that is linked to the amplification of anthropogenic skyglow during the winter months due to climatological conditions.